A Case Study Of Risk Evaluation At Cerrejon Mine - Luis-Fernando Contreras; Richard LeSueur; Juliano Maran (The Southern African Institute of Mining and Metallurgy, 2006)
A risk study was carried out at the Cerrejon coal mine in order to assess the impacts of pit slope failure in terms of safety of personnel and destruction of equipment with economic consequences. Results of the assessment enabled the definition of risk treatment requirements and the identification of key aspects to consider in a risk treatment plan. The approach included the following tasks: (1) Assessment of the total probability of failure (POF) representative of the stability conditions of typical footwall and highwall slopes. For this purpose, stability analyses were carried out to define the Design POF, which accounts for the variability of strength parameters and represents the normal conditions considered for slope design. Strength parameters for highwall slope analysis were derived from borehole data obtained with a geotechnical drilling campaign. The Total POF was estimated through the use of Source Response Diagrams (SRD) in order to incorporate other sources of uncertainty not accounted for, like changes in geometry, variability of rock conditions due to geological or operational factors, changes in groundwater conditions and occurrence of seismic events. (2) Assessment of the consequences of footwall and highwall slope failure on safety of personnel. The assessment was performed through the use of event tree analysis to establish the probability of fatality caused by slope failures, from the Total POF defined in the previous task. This analysis required the evaluation of personal exposure to slope failures. Also, the assessment included benchmarking of acceptability criteria in terms of probability of fatality and the evaluation of options of risk mitigation to comply with these criteria. (3) Assessment of the consequences of footwall and highwall slope failure in terms of economic losses associated with impact on equipment. The analysis included the evaluation of equipment exposure to slope failures, and it was performed through event tree analysis to establish the probability of an economic loss associated to total or partial lost of equipment, from the total POF value defined in the first task. The magnitude of the economic losses was estimated from the costs of damaged equipment, lost production and site restoration. Options of risk mitigation were also examined in terms of economic losses. The risk assessment process applied to the Cerrejón mine showed how the system can be applied to evaluate the consequences of failure in terms of personnel safety and economics and to identify the more adequate risk mitigation options. The system can be an extremely powerful tool in the mine design process and provides the opportunity to rationalize the geotechnical information requirements, once the risk criteria have been defined by management. The main purpose of this paper is to present the process; therefore, the emphasis has been put on the methodology followed rather than on the actual results obtained.